Family resources and Support to Families of Children with Intellectual Disability (Annual of the Faculty of Philosophy in Skopje, 2017)
Families with a member with intellectual disability, especially when it comes to severe intellectual disability, which is usually accompanied by additional disorders, need continuous help and support.The survey aims to show which are the resources available to the family and from whom the families of children with intellectual disabilities are most supported.Within this research, data from 60 parents of children with intellectual disability from the four day centres from Ohrid and Kumanovo were obtained using the Family Support Scale and the Family Resources Scale.With the help of AN OVA and the t-test for the significance of differences, it was found that the respondents have the biggest support from their partner. Day centres are an important resource that plays an essential role in the lives of children with special educational needs and their families. Data from the survey showed that to the parents most important is the time they spend with their children and the least time remains for rest, relaxation and fun. Corresponding with the expected, there is a correlation between resources and family support, that is, how much support increases, the resources increase. The age of the child is the only variable affecting family support and the resources depends on the level of the parent ’s education.Families of children with special educational needs need more psychological support and counseling, social and educational support, support in the realization of rights in the field of social and health care, as well as greater support from the local community.
Keywords: CHILDREN WITH INTELLECTUAL DISABILITY; DAY CARE CENTRES; FAMILY SUPPORT; FAMILY RESOURCES